Propelling efficiency in sprint front crawl swimming - Toussaint, H. M.; van der Meer, S.; de Niet, M.; Truijens, M. (Biomechanics and Medicine in Swimming X, 2006)
In swimming, generation of propulsion will always lead to a loss of mechanical energy, which is used to give fluid a kinetic energy change. Consequently, not all of the total mechanical power (Po) generated by the swimmer is available to overcome drag. The propulsive efficiency (ep) is defined as ratio of the power to overcome drag (Pd) relative to the total mechanical power. Previously, ep was measured using oxygen uptake measurement techniques that could only be used at slow speeds. In a group of top-level swimmers an average ep value of 63.5% (range 50 - 77%) was found at a swimming speed of 1.29 m•s-1. In the present demonstration a new approach to measure ep at higher speeds is presented and evaluated. The system to Measure Active Drag (MAD-system) provides fixed push of pads below the water enabling propulsion generation without loss of energy to the water. Therefore, all-out sprints performed on the M.A.D.-system enabled faster swimming than all-out sprints swimming `free`. Considering that power to overcome drag relates to swimming speed cubed and assuming equal power output in two 25 m sprints (free and MAD), the ratio of speed cubed sprinting all-out `free` relative to the speed cubed sprinting all-out on the M.A.D.-system reflects ep. For the thirteen elite swimmers ep values of on average 75% (range 68 - 84%) for an average speed of 1.64 m•s-1 were found. This compares reasonably well with the previously reported values. The determination of ep based on two sprints free and two sprints on the M.A.D. system, is fast and can be incorporated in a test to evaluate changes in performance factors with training.